2023
DOI: 10.1002/1878-0261.13427
|View full text |Cite
|
Sign up to set email alerts
|

Targeting mitochondrial energetics reverses panobinostat‐ and marizomib‐induced resistance in pediatric and adult high‐grade gliomas

Abstract: In previous studies, we demonstrated that panobinostat, a histone deacetylase inhibitor, and bortezomib, a proteasomal inhibitor, displayed synergistic therapeutic activity against pediatric and adult high‐grade gliomas. Despite the remarkable initial response to this combination, resistance emerged. Here, in this study, we aimed to investigate the molecular mechanisms underlying the anticancer effects of panobinostat and marizomib, a brain‐penetrant proteasomal inhibitor, and the potential for exploitable vul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 107 publications
0
1
0
Order By: Relevance
“…Subsequent investigation revealed that the highly integrated tricarboxylic (TCA) cycle of Marizomib ® with panobinostat, which upregulated glycolysis and activated the energy metabolism to replenish the supply of ATP for cell growth and survival, was responsible for the observed resistance to the drug in glioma-resistant cells. These findings call for more research on treating glioma-resistant cells by focusing on metabolic vulnerability [ 319 ].…”
Section: Marine Actinobacteriamentioning
confidence: 99%
“…Subsequent investigation revealed that the highly integrated tricarboxylic (TCA) cycle of Marizomib ® with panobinostat, which upregulated glycolysis and activated the energy metabolism to replenish the supply of ATP for cell growth and survival, was responsible for the observed resistance to the drug in glioma-resistant cells. These findings call for more research on treating glioma-resistant cells by focusing on metabolic vulnerability [ 319 ].…”
Section: Marine Actinobacteriamentioning
confidence: 99%
“…Mutations of isocitrate dehydrogenase (IDH) one and 2 impair the decarboxylation of α-KG to isocitrate and enhance the production of 2-hydroxyglutarate (2HG) ( Jane et al, 2023 ). This enzymatic disruption leads to elevated DNA methylation levels, a phenomenon frequently observed in diseases such as acute myeloid leukemia (AML) ( Wilde et al, 2019 ; Pei et al, 2023 ).…”
Section: Targeting Glucose Metabolismmentioning
confidence: 99%